Measurement Optimization for Parameter Estimation in Distributed Systems - Uciński, Dariusz (Zielona Góra: Technical University Press)
This book is organized as follows. In Chapter 1 a brief summary of concrete applications involving the sensor location problem is given. Some of these examples are used throughout the monograph to motivate and illustrate the demonstrated developments. A concise general review of the existing literature and a classication of methods for optimal sensor location are presented
Keywords: analiza numeryczna; optymalizacja; czujniki; pomiary; równanie różniczkowe